2006
DOI: 10.1093/cercor/bhl078
|View full text |Cite
|
Sign up to set email alerts
|

The Parahippocampal Cortex Mediates Spatial and Nonspatial Associations

Abstract: The parahippocampal cortex (PHC) has been implicated in the processing of place-related information. It has also been implicated in episodic memory, even for items that are not related to unique places. How could the same cortical region mediate such seemingly different cognitive processes? Both processes rely on contextual associations, and we therefore propose that the PHC should be viewed not as exclusively dedicated for analyzing place-related information, or as solely processing episodic memories, but ins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

38
255
2
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 313 publications
(296 citation statements)
references
References 70 publications
38
255
2
1
Order By: Relevance
“…The major aspects of this default network overlap remarkably with the same regions that we have found as directly related to contextual associative activation (figure 3; Bar & Aminoff 2003;Aminoff et al 2007;Bar et al 2007). This overlap between the default network and the network subserving associative processing of contextually related information is taken as the cortical manifestation that associative predictions are crucial, ongoing, elements of natural thought.…”
Section: Associations: the Building Blockssupporting
confidence: 74%
See 1 more Smart Citation
“…The major aspects of this default network overlap remarkably with the same regions that we have found as directly related to contextual associative activation (figure 3; Bar & Aminoff 2003;Aminoff et al 2007;Bar et al 2007). This overlap between the default network and the network subserving associative processing of contextually related information is taken as the cortical manifestation that associative predictions are crucial, ongoing, elements of natural thought.…”
Section: Associations: the Building Blockssupporting
confidence: 74%
“…On one extreme, associations are automatic, simple and unique, similar to a basic Hebbian association where associated concepts are co-activated when the representation of one of them is activated. Such associations have been the primary focus of research, and have largely been shown to be mediated by the MTL (Petrides 1985;Schacter 1987;Miyashita 1993;Shallice et al 1994;Eichenbaum & Bunsey 1995;Suzuki & Eichenbaum 2000;Stark & Squire 2001;Sperling & Chua 2003;Ranganath et al 2004;Aminoff et al 2007). Other associations are more deliberative, and their selective co-activation depends on the specific context in which they are embedded (Bar 2004).…”
Section: Associations: the Building Blocksmentioning
confidence: 99%
“…Recent studies suggest a role for the parahippocampal cortex region in more complex spatial processing, such as scenes (Buffalo et al, 2006;Henderson et al, in press;Epstein et al, 2007) and other contextual stimuli (Aminoff et al, 2007). Thus, although the current spatial task may be regarded as depending on a spatial processing system per se, it may not have involved sufficiently complex visual stimuli to engage the posterior MTL region.…”
Section: Discussionmentioning
confidence: 92%
“…This finding subsequently was extended to reveal that the parahippocampal cortex is also activated during viewing of famous faces, wherein the contextual associations are not typically place-specific but rather associated with rich pictorial and abstract contextual information (Bar et al, 2008). In addition, the distinction between spatial and nonspatial contextual activation was clarified in a study that compared activations to simple visual patterns where the contextual associations were explicitly trained (Aminoff et al, 2007). Under the spatial context condition, three patterns were repeatedly presented together in the same spatial configuration on a computer screen.…”
Section: The Role Of the Parahippocampal/ Postrhinal Cortex And Mediamentioning
confidence: 91%